Pengembangan Mobile Learning Berbantuan Kodular Untuk Meningkatkan Kemampuan Pemahaman Matematis Siswa Kelas X - Sadiyah, Ulim Fatma; Kumala, Fitria Zana (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
The lack of understanding of mathematics in class X SMA Muhamadiyyah 1 Purbalingga triggered this research. The average score of the initial test of students' mathematical understanding abilities that the researchers conducted was 59.6. Interviews with mathematics teachers in class X showed that textbooks were the only form of teaching material. The aim of this research is to create Android-based mobile learning media on opportunity material aimed at improving the mathematical understanding of class X students. Samples were taken from two classes to become the research population (X-A, experimental, X-B control) in class Based on the research results, class X students benefited from using Android-based mobile learning media on opportunity material. Experts in the field validate the media level at 90.00%. Teacher response reached 80%. Prerequisite tests, including normality and homogeneity, were carried out before the sample t test was carried out to show that, at a Sig (2-tailed) significance level of 0.000 0.05, there was a difference in the average N-Gain scores between the two groups. This shows that H1 is accepted and H0 is rejected. The average N-Gain score for the experimental class was 0.76, higher than the N-Gain score for the control class, which was 0.265. The results show that the Android-based mobile learning learning media uses opportunity material. Class X students of SMA Muhamadiyyah 1 Purbalingga showed a significant increase in mathematical understanding after using Android-based mobile learning.  Keywords: Mobile Learning, Learning Media, Mathematical Understanding